Immunoinformatics-Based Designing of a Multi-Epitope Chimeric Vaccine From Multi-Domain Outer Surface Antigens of Leptospira - Kumar, Pankaj; Lata, Surabhi; Shankar, Umate Nachiket; Akif, Mohd. (Frontiers in Immunology, 2021)
Accurate information of antigenic epitopes within multi-domain antigen would provide insight into the vaccine design and immunotherapeutic. Multi-domain outer surface Leptospiral immunoglobulin- like (Lig) proteins, LigA and LigB, consist of 12-13 homologous bacterial Ig (Big) like domains, are potential antigens of Leptospira interrogans. Currently, no effective vaccine is available against pathogenic leptospira. Both humoral and cell mediated immunity of the host play a critical role in defending against leptospira infection. Here, we used immunoinformatics approaches to evaluate antigenic BCL and TCL epitopes from Lig proteins. Based on certain crucial parameters, potential epitopes that can stimulate both types of adaptive immune response were selected to design a chimeric vaccine construct. Additionally, an adjuvant, mycobacterial heparin-binding hemagglutinin (HBHA), was incorporated to the final multi-epitope vaccine construct with a suitable linker. The final construct was further scored for its antigenicity, allergenicity and physicochemical parameters. A three-dimensional modelled construct of the vaccine was implied to interact with toll-like receptor 4 (TLR4) using molecular docking. The stability of the vaccine construct with the TLR4 was predicted by molecular dynamics simulation. Our results demonstrate application of immunoinformatics and structure biology strategies to develop an epitope specific chimeric vaccine from the multi-domains proteins. The current finding will be useful for future experimental validation to ratify the immunogenicity of the chimera.